ANALISIS KINERJA KEUANGAN UD OIHAYAITA - Fau, Jhon Firman; Buulolo, Progresif (LPPM Universitas Nias Raya, 2022)
Assessment of the company's financial performance needs to be carried out as a means or indicator to improve the company's operational activities so that the company can experience better financial growth and be able to compete with other companies. This study aims to determine the results of UD OIHAYAITA's financial statements for 3 years (2019-2021), the type of data in this study is secondary data in the form of financial reports every month, so the amount of data is 36 months. The analytical methods used in this research are Net Profit Margin (NPM), Gross Profit Margin (GPM), and Inventory Turn Over. The results showed that the Net Profit Margin from January 2019 to December 2021 fluctuated, with an average Net Profit Margin of 0.28 times, and an average Gross Profit Margin of 0.54 times while Inventory Turn Over an average of 2.34 times. UD OIHAYAITA company has not been able to optimize profit, because the ultimate goal of achieving a company is to obtain maximum profit.